Two new scorpion species of genus Brachistosternus (Scorpiones: Bothriuridae) from northern Chile - Ojanguren-Affilastro, Andrés A.; Agusto, Pablo; Pizarro-Araya, Jaime; Mattoni, Camilo I. (Zootaxa, 2007)
Brachistosternus (Leptosternus) cepedai n. sp. and Brachistosternus (Leptosternus) coquimbo n. sp. are described from Coquimbo region, in northern Chile. Brachistosternus cepedai n. sp. occurs in coastal dunes and is closely related to Brachistosternus (L.) sciosciae Ojanguren-Affilastro, 2002. On the other hand, Brachistosternus coquimbo n. sp occurs at high altitudes in the Andes mountain chain and is related to Brachistosternus (L.) montanus Roig Alsina, 1977, and to several Andean species from Argentina and Chile. Adaptative characters of the psammophilous Br. (L.) cepedai n. sp. are discussed. 39 scorpion species are now known from Chile, ten of them occur in the Coquimbo Region, being the region with the more diverse scorpion fauna in the country.